1995
DOI: 10.1159/000173900
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Pathways for ATP-lnduced Intracellular Calcium Elevation in Pheochromocytoma (PC12) Cells

Abstract: Extracellular ATP excites neurons in both the peripheral and central nervous system. To elucidate the mechanisms involved, we used spectrofluorometric analysis to study the pathways by which extracellular ATP elevates the intracellular Ca2+ concentration ([Ca2+]i) in individual, fura-2-loaded, rat pheochromocytoma PC12 cells. ATP ( > 1 µM) increased [Ca2+]i. The ATP effect on [Ca2+]i was completely abolished by a nominally Ca2+ Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Since the L-type and N-type Ca 2+ channels are expressed in the PC12 cells [26], we tested whether cyanidin-3-glucoside affects the ATP-induced secondary Ca 2+ influx through voltage-gated L-type and N-type Ca 2+ channels (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…Since the L-type and N-type Ca 2+ channels are expressed in the PC12 cells [26], we tested whether cyanidin-3-glucoside affects the ATP-induced secondary Ca 2+ influx through voltage-gated L-type and N-type Ca 2+ channels (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…In PC12 cells, ATP induces Ca 2+ influx through the secondary activation of voltage-gated Ca 2+ channels following depolarization of the membrane by the ATP-induced activation of non-selective cation channels [34]. In addition to L-type voltage-dependent Ca 2+ channels, it has been reported that ATP can induce a [Ca 2+ ]i increase in PC12 cells through dihydropyridine-and CTXinsensitive-voltage-dependent Ca 2+ channels [34]. In this study, octyl gallate inhibited high KCl-induced [Ca 2+ ]i increase.…”
Section: Discussionmentioning
confidence: 99%